Abba Ptachya Lerner papers - Lerner, Abba Ptachya, 1903-; Lerner, Daliah Goldfarb
Correspondence, memoranda, diary and dream notes, writings, speeches, reports, interviews, research materials, family papers, legal papers, genealogical material, newspaper clippings, printed materials, drawings, photographs, and other papers relating primarily to Lerner's activities as professor, lecturer, and advisor in the field of economics. Topics include economic policy, economic theories of John Maynard Keynes, money, peace in the Middle East, Lerner's work for Rand Corporation, wealth, and welfare economics. Of special note is Lerner's letter (1979 December 26) to the ayatollah Ruhollah Khomeini encouraging reestablishment of peaceful relations between Iran and the U.S. and the release of the American hostages. Also includes papers relating to Lerner's interest in art, particularly photography, mobiles, and pen and ink drawings; and papers of his wife, Daliah Goldfarb Lerner.
Correspondents include Haim Ben-Shahar, Raymond L. Buell, Arthur E. Burns, David C. Colander, Gerald R. Ford, Milton Friedman, John Kenneth Galbraith, Alfred E. Kahn, William Proxmire, Alice M. Rivlin, and Robert A. Taft, Sr.
Library of Congress Prints and Photographs Division.
Economist and educator. Died 1982.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ben-Shahar, Haim -- Correspondence; Buell, Raymond Leslie, -- 1896-1946 -- Correspondence; Burns, Arthur Edward, -- 1908-1986 -- Correspondence; Colander, David C. -- Correspondence; Ford, Gerald R., -- 1913-2006 -- Correspondence; Friedman, Milton, -- 1912-2006 -- Correspondence; Galbraith, John Kenneth, -- 1908-2006 -- Correspondence; Kahn, Alfred E. -- Correspondence; Khomeini, Ruhollah -- Correspondence; Proxmire, William -- Correspondence; Rivlin, Alice M. -- Correspondence; Taft, Robert A. -- 1889-1953 -- Correspondence; Rand Corporation; Art; Drawing; Economics; Economics -- Study and teaching; Iran Hostage Crisis, 1979-1981.; Keynesian economics; Mobiles (Sculpture); Money; Photography; Wealth; Welfare economics; Iran -- Foreign relations -- United States; Middle East -- Foreign relations; United States -- Economic policy; United States -- Foreign relations -- Iran; Economists; Educators